Cage-lid hanging behavior as a translationally relevant measure of pain in mice. Issue 5 (May 2021) - Zhang, Hantao; Lecker, Irene; Collymore, Chereen; Dokova, Anastassia; Pham, Maian Christine; Rosen, Sarah F.; Crawhall-Duk, Hayley; Zain, Maham; Valencia, Megan; Filippini, Helena Fetter; Li, Jerry; D'Souza, Abigail J.; et al.
Abstract : Abstract: The development of new analgesic drugs has been hampered by the inability to translate preclinical findings to humans. This failure is due in part to the weak connection between commonly used pain outcome measures in rodents and the clinical symptoms of chronic pain. Most rodent studies rely on the use of experimenter-evoked measures of pain and assess behavior under ethologically unnatural conditions, which limits the translational potential of preclinical research. Here, we addressed this problem by conducting an unbiased, prospective study of behavioral changes in mice within a natural homecage environment using conventional preclinical pain assays. Unexpectedly, we observed that cage-lid hanging, a species-specific elective behavior, was the only homecage behavior reliably impacted by pain assays. Noxious stimuli reduced hanging behavior in an intensity-dependent manner, and the reduction in hanging could be restored by analgesics. Finally, we developed an automated approach to assess hanging behavior. Collectively, our results indicate that the depression of hanging behavior is a novel, ethologically valid, and translationally relevant pain outcome measure in mice that could facilitate the study of pain and analgesic development. Abstract : Supplemental Digital Content is Available in the Text.Cage-lid hanging behavior is impaired by sustained pain in mice and can be used as an ethologically valid and translationally relevant pain outcome measure.